Handbook of systems engineering and management - Sage, Andrew P.; Rouse, William B. (John Wiley & Sons, 1999)
Focus in this book is placed on systems engineering and systems management for building systems of all types. The role of these systems to produce high reliability, and quality services and products is stressed. The role of advanced information technologies in enhancing productivity and quality is also discussed.